Understanding Chemotherapy Adherence in Breast Cancer Patients: A Multidimensional Review through the WHO Adherence Framework - Sayani, Lamha (Asian Pacific Journal of Cancer Biology, 2025)
Background: Breast cancer is the most prevalent cancer globally and a major public health challenge in low and middle-income countries (LMIC) like Pakistan. Despite advances in treatment, poor adherence to chemotherapy remains a concern, affecting survival, recurrence and quality of life. Adherence is influenced by individual, social, cultural and systemic factors. Objective: This review uses the WHO-Multidimensional Adherence Model (WHO-MAM) to identify key factors influencing chemotherapy adherence among breast cancer patients in LMICs. It aims to highlight underexplored domains particularly behavioural and cultural influences and suggest directions for targeted interventions and policy development. Methods: This scoping review was conducted using literature published between 2019 and 2025, sourced from PubMed, Scopus and Google Scholar. A total of 51 full-text articles were reviewed, 20 articles were included based on relevance to chemotherapy adherence and applicability to LMIC settings. Key Findings: Chemotherapy adherence is influenced by socioeconomic barriers (e.g., financial constraints, low education), healthcare system limitations (e.g., poor provider communication, limited oncology access), and treatment-related challenges (e.g., side effects). Patient-related factors such as mental health, perceived stigma, and cultural beliefs are significant but underexplored, especially in South Asia. Conclusion: Improving chemotherapy adherence requires patient-centred, culturally informed strategies and health system reforms. Greater attention to behavioural and cultural factors is essential for designing interventions that are both practical and effective in LMIC settings.